Suppression of auto-fluorescence from high-resolution 3D polymeric architectures fabricated via two-photon polymerization for cell biology applications - Sharaf, A.; Frimat, J.P.; Kremers, G.J.; Accardo, A. (Micro and Nano Engineering, 2023)
Two-photon polymerization (2PP) has provided the field of cell biology with the opportunity to fabricate precisely designed microscaffolds for a wide range of studies, from mechanobiology to in vitro disease modelling. However, a multitude of commercial and in-house developed photosensitive materials employed in 2PP suffers from high auto-fluorescence in multiple regions of the spectrum. In the context of in vitro cell biological studies, this is a major problem since one of the main methods of characterization is fluorescence microscopy of immuno-stained cells. This undesired auto-fluorescence of microscaffolds affects the efficiency of such an analysis as it often overlaps with fluorescent signals of stained cells rendering them indistinguishable from the scaffolds. Here, we propose two effective solutions to suppress this auto-fluorescence and compare them to determine the superiority of one over the other: photo-bleaching with a powerful UV point source and auto-fluorescence quenching via Sudan Black B (SBB). The materials used in this study were all commercially available, namely IP-L, IP-Dip, IP-S, and IP-PDMS. Bleaching was shown to be 61.7–92.5% effective in reducing auto-fluorescence depending on the material. On the other hand, SBB was shown to be 33–95.4% effective. The worst result in presence of SBB (33%) was in combination with IP-PDMS since the adsorption of the material on IP-PDMS was not sufficient to fully quench the auto-fluorescence. However, auto-fluorescence reduction was significantly enhanced when activating the IP-PDMS structures with oxygen plasma for 30 s. Moreover, we performed a cell culture assay using a human neuroblastoma cell line (SH-SY5Y) to prove the effectiveness of both methods in immunofluorescence characterization. SBB presented a lower performance in the study especially in presence of 2PP-fabricated microchannels and microcages, within which the differentiated SH-SY5Y cells migrated and extended their axon-like processes, since the SBB obstructed the fluorescence of the stained cells. Therefore, we concluded that photo-bleaching is the optimal way of auto-fluorescence suppression. In summary, this study provides a systematic comparison to answer one of the most pressing issues in the field of 2PP applied to cell biology and paves the way to a more efficient immunofluorescence characterization of cells cultured within engineered in vitro microenvironments. [Display omitted] •Auto-fluorescence of photoresins is supressed by UV-bleaching and fluorescence quenching.•Plasma treatment of IP-PDMS enhances Sudan Black B adsorption.•Visualization of stained cells is significantly enhanced in treated microstructures.•UV-bleaching is superior to quenching for intrinsic polymer fluorescence suppression.